A clinical assessment of the Mucus Shaver, a device to keep the endotracheal tube free from secretions - Berra, Lorenzo (2012)
OBJECTIVE: We evaluated a new device designed to clean the endotracheal tube (ETT) in mechanically ventilated patients: the Mucus Shaver. DESIGN: Prospective, randomized trial. SETTING: University hospital intensive care unit. PATIENTS: We enrolled 24 patients, expected to remain ventilated for more than 72 hours. INTERVENTIONS: The Mucus Shaver is a concentric, inflatable catheter for the removal of mucus and secretions from the interior surface of the ETT. The Mucus Shaver is advanced to the distal ETT tip, inflated and subsequently withdrawn over a period of 3–5 seconds. Patients were prospectively randomized, within 2 hours of intubation, to receive standard ETT suctioning treatment or standard suctioning plus Mucus Shaver use, until extubation. MEASUREMENTS AND MAIN RESULTS: During the study period, demographic data, recent medical history, adverse events and staff evaluation of the Mucus Shaver were recorded. At extubation, each ETT was removed, cultured and analyzed by Scanning Electron Microscopy (SEM). 12 patients were assigned to the study group and 12 to the control group. No adverse events related to the use of the Mucus Shaver were observed. At extubation, only 1 ETT from the Mucus Shaver group was colonized, while in the control group, 10 ETTs were colonized (8% vs. 83%; p<0.001). SEM showed little secretions on the ETTs from the study group, while thick bacterial deposits were present on all the ETTs from the control group (p<0.001 by Fisher’s exact test, using a maximum biofilm thickness of 30 µm as cut-off). The nursing staff was satisfied by the overall safety, feasibility, and efficacy of the Mucus Shaver. CONCLUSIONS: The Mucus Shaver is a safe, feasible and efficient device for ETT cleaning in the clinical setting. The Mucus Shaver is helpful in preventing ETT colonization by potentially harmful microorganisms.